Penerapan Model Pembelajaran Kontekstual Untuk Meningkatkan Keterampilan Menulis Biografi - Yulia Yulia; Eri Sarimanah; Suhendra Suhendra (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The study is aimed at investigating the implementation of Contextual Learning Model in improving students’ ability and their obstacles to write biography. The study was conducted to the students of SMPN 2, Kabandungan, Kabupaten Sukabumi grade VII. Experimental method was employed. There were a control class and an experimental class. The data was collected through test and questionnaire. The sample was taken by using saturated sampling technique. The first hypothesis which stated that the model of contextual learning could improve the ability of students at SMPN 2, Kabandungan, Kabupaten Sukabumi grade VII to write biography is proven to be true. It could be seen from the students’ score of pretest in the experimental class whose average reached 51,0 while the average of the posttest score was 78,3. The average score of students’ pretest in the control class was 47,4 and the model of students as facilitator and explaining was implemented. At the end, the average score of the post test was 65,6. From the score gained, it is clear that the model of contextual learning was more effective to improve students’ ability in writing biography. Based on the mean calculation using t-test formula, it was gained that to =3,72, t0,95=1,67 and the value of t0,99=2,39. It means that to is higher than tt with the comparison of 1,67 less than 3,72 more than 2,39. It clearly shows that the contextual model implemented in the experimental class could improve the students’ biography writing skill. The second hypothesis which stated that the students encountered problems in writing biography was also proven to be true. Based on the result of questionnaire analysis, there were 71% of the students encountering problems in developing the identity of the character, 54% encountering problems in applying the grammar of writing biography, and 49% students encountering problems when they explained the great attitudes of the character. Therefore, it can be concluded that the contextual learning model could improve students’ ability to write biography even though the students still encountered problems.